STUDENT RECEPTION ON THE IMPLEMENTATION OF ONE DAY ONE PAGE: STUDY LIVING QUR’AN AT PONDOK PESANTREN - Najiburrohman, Najiburrohman; Hasanah, Fitriyatul (Universitas Nurul Jadid, 2022)
This research is a study of the living Qur’an, which aims to determine the reception of students towards implementing One Day One Page (ODOP) activities in the Al-Lathifiyah area of the Pondok Pesntren Nurul Jadid, Paiton, Probolinggo, East Java. The method used in this research is a descriptive qualitative method with data collection techniques using observation and interviews that interact directly with data sources. The object of research in this study were students and administrators who participated and were involved in these activities. This study concluded that the students responded very well to this One Day One Page (ODOP) activity. They feel that activities have an essential role in their ability to read the Koran and the ability to read the yellow book they are studying.